2020
DOI: 10.1002/app.49637
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different zeolitic imidazolate frameworks nanoparticle‐modified β‐FeOOH rods on flame retardancy and smoke suppression of epoxy resin

Abstract: A simple method was used to load zeolitic imidazolate frameworks (ZIFs) onto β-FeOOH nanorods to ameliorate the flame retardancy and smoke suppression of epoxy resin (EP). The morphology and structure of ZIF-8-β-FeOOH (Z8Fe) and ZIF-67-β-FeOOH (Z67Fe) nano hybrids were systematically characterized by field emission scanning electron microscope, Fourier transform infrared and Xray diffraction (XRD) spectra, which proved the successful preparation of the hybrids. 3 wt% of Z8Fe and Z67Fe were added to the EP matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The peak intensity of BPEI-ZIF-8 was lower than that of ZIF-8, which might be due to the decrease in ZIF-8 content and the enhancement in the interaction between the PEI and Zn 2+ sites [46][47][48]. These results were consistent with previous reports [20,46], demonstrating successful syntheses of ZIF-8 and BPEI-ZIF-8.…”
Section: Characterization Of Bpei-zif-8/il Nanoparticlessupporting
confidence: 90%
See 1 more Smart Citation
“…The peak intensity of BPEI-ZIF-8 was lower than that of ZIF-8, which might be due to the decrease in ZIF-8 content and the enhancement in the interaction between the PEI and Zn 2+ sites [46][47][48]. These results were consistent with previous reports [20,46], demonstrating successful syntheses of ZIF-8 and BPEI-ZIF-8.…”
Section: Characterization Of Bpei-zif-8/il Nanoparticlessupporting
confidence: 90%
“…ZIF-8 is the most investigated among the various ZIFs. Previous research has shown that ZIF-8 can be used for toughening resins due to its high specific surface area, low dielectric constant, and low polarity [19][20][21]. However, like other nanoparticles, ZIF-8 faces the challenge of being uniformly dispersed in the resin matrix for achieving an excellent modification due to the same problem of agglomeration.…”
Section: Introductionmentioning
confidence: 99%
“…Then, 2-MI solution was added to it, with the pH stabilised at 8.5. After standing for several hours, the precipitate was collected, washed with deionised water several times, and then dried at 80°C for 8 h to obtain ZIF-67-β-FeOOH (ZF) [26].…”
Section: Methodsmentioning
confidence: 99%
“…have catalytic carbonization properties, pristine MOF monomers can be added directly to the polymer matrix as flame retardants. During combustion, the metal sites of MOFs generate metal oxides that promote the formation of a continuous dense char layer to insulate part of the combustible gases and heat [ 28 ]. Shi et al added synthetic zeolitic imidazolate framework-8 (ZIF-8) nanoparticles directly into poly (lactic acid) (PLA), and an addition of 0.2 wt% could increase the limiting oxygen index value from 20.5% to 23.5% [ 29 ].…”
Section: Pristine Mofs Directly As Flame Retardantsmentioning
confidence: 99%